2018
DOI: 10.4018/978-1-5225-2639-1.ch005
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Engagement in Educational Technologies Through Developmental Theory and Program Data

Abstract: This chapter provides theoretical and practical insights for integrating and improving motivation in the design of educational technologies and enhancement of student engagement. While the number of new products available to support differentiated learning is great news for students, the rapid development of products may mean quantity over quality. Schools may end up purchasing educational technology tools that may not necessarily be user-friendly, developmentally appropriate, or built with the student end-use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Broadly, reading interest and motivation in the early preschool years predict later literacy achievement (Ilie & Lietz, 2010;Scarborough & Dobrich, 1994), and theoretical work suggests that technology might be particularly suited to spark motivation by fostering autonomy and competence (Kazakoff et al, 2018). Research with older "reluctant readers" noted that this population found eBooks more engaging than traditional books, and eBook use led to increased time reading and parent perceptions of reading ability (Oakley & Jay, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Broadly, reading interest and motivation in the early preschool years predict later literacy achievement (Ilie & Lietz, 2010;Scarborough & Dobrich, 1994), and theoretical work suggests that technology might be particularly suited to spark motivation by fostering autonomy and competence (Kazakoff et al, 2018). Research with older "reluctant readers" noted that this population found eBooks more engaging than traditional books, and eBook use led to increased time reading and parent perceptions of reading ability (Oakley & Jay, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Edtech further has the potential to be highly motivating for students (Kazakoff et al, 2018)-motivation that in turn can promote stronger learning outcomes (Schiefele et al, 2012). In a review, Kazakoff et al (2018) note that Core5 fosters motivation by allowing students to choose which reading skill they want to practice in a given session, monitor their learning via progress bars, receive in-program scaffolds so they have a successful learning experience, and earn certificates as they complete levels. Kazakoff and associates conclude these features might create a safe learning space for students with reading difficulties.…”
Section: Promise Of Edtechmentioning
confidence: 99%